Status of NGOs in International Humanitarian Law. - Barrat, Claudie (Graduate Institute of International and Development Studies., 2014)
In Status of NGOs in International Humanitarian Law, Claudie Barrat examines the legal framework applicable to NGOs in situations of armed conflict.